2017
DOI: 10.1016/j.jtcvs.2017.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following thoracotomy or thoracoscopic vascular ring division in children and young adults

Abstract: Vascular ring division by either thoracotomy or VATS can be performed with low rates of complication and need for reintervention. Compared with thoracotomy, VATS is associated with shorter operative duration and hospital LOS among patients with RAA with LSCA/LL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
4
16
0
Order By: Relevance
“…To investigate postoperative complications, operation duration, and total length of hospital stay following the use of the minimally invasive VATS technique in children for the division of vascular rings, Herrin et al conducted a retrospective study of patients who underwent vascular ring division through conventional thoracotomy or minimally invasive VATS at their institution. 10 A total of 115 children (median age 2.7 years) underwent vascular ring division via VATS, while 85 patients underwent the conventional thoracotomy. VATS repairs were associated with significantly shorter operations and length of stay and improved cosmetic outcomes, as well as comparable incidence of major complications, including chylothorax and vocal cord paralysis, when compared to traditional thoracotomy.…”
Section: Vascular Ring Divisionmentioning
confidence: 99%
“…To investigate postoperative complications, operation duration, and total length of hospital stay following the use of the minimally invasive VATS technique in children for the division of vascular rings, Herrin et al conducted a retrospective study of patients who underwent vascular ring division through conventional thoracotomy or minimally invasive VATS at their institution. 10 A total of 115 children (median age 2.7 years) underwent vascular ring division via VATS, while 85 patients underwent the conventional thoracotomy. VATS repairs were associated with significantly shorter operations and length of stay and improved cosmetic outcomes, as well as comparable incidence of major complications, including chylothorax and vocal cord paralysis, when compared to traditional thoracotomy.…”
Section: Vascular Ring Divisionmentioning
confidence: 99%
“…Furthermore, when Kommerell diverticulum excluded, they have reported only 8 cases that required re-intervention in overall 350 cases. Similarly, Herrin et al (22) reported necessity of re-invervention in 8 of total 200 cases (115 VATS and 85 thoracoscopy). Seven of these had aortopexy and only two of them were operated via thoracosopy previously.…”
Section: Discussionmentioning
confidence: 91%
“…Approximately, 70-75% of symptoms disappear in early period following surgery. (22)(23) Bertolini et al (23) evaluated that the remaining symptoms, which are approximately %30, tend to disappear at a later period. We also had no residual symptoms except for one case suffering from asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The association between thoracoscopy and shorter hospitalisation has been observed in prior studies 6,8 as well as other lesions, including vascular rings. 13 However, there is some disagreement in the literature, as other groups have reported no difference, although these either had fewer patient numbers or had focused on neonates and infants rather than patients receiving elective surgery. 5,7 In contrast, there does appear to be general agreement regarding an association between thoracoscopy and reduced ICU stay.…”
Section: Discussionmentioning
confidence: 99%